Sex pheromone of Argyrotaenia pomililiana (Lepidoptera: Tortricidae), a leafroller pest of apples in Argentina - Cichon, Liliana; Trematerra, Pascuale; Coracini, Myrian D. A.; Fernandez, Dario Eduardo; Bengtsson, Marie; Witzgall, Peter (Oxford University Press, 2025)
Sex pheromone gland extracts of Argyrotaenia pomililiana Trematerra & Brown females contained seven 14-chain compounds, the Z and E isomers of 11-tetradecenyl acetate, 11-tetradecen-1-ol, and 11-tetradecenal, respectively, together with tetradecyl acetate. In field trapping tests, a 100:5 blend of Z11–14:Ac and Z11–14:Al was shown to be suitable for detection and monitoring of A. pomililiana. This species-specific lure will facilitate the use of mating disruption against codling moth, Cydia pomonella (L.), in Argentine fruit orchards.